2016
DOI: 10.18632/oncotarget.13410
|View full text |Cite
|
Sign up to set email alerts
|

New conception for the development of hypertension in preeclampsia

Abstract: Placental vascular dysfunction was suggested to be critical for placental ischemia-initiated hypertension in preeclampsia, although the contributions of endothelium involved are unclear. The present study found, unlike non-placental vessels, acetylcholine showed no vasodilatation effect on placental vessels, indicating that endothelial-derived nitric oxide (NO) was extremely weak in placental vessels. Placental vascular responses to exogenous NO from sodium nitroprusside (SNP) were significantly different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…It is important to note, however, that NO still plays a role in the vasodilation of the placental vasculature. Indeed, endothelium‐independent vasodilation, expressed as the vasodilatory response to the NO donor SNP, although reduced, was still present in preeclamptic placental vessels . This indicated that it might be the smooth muscle portion of the NO‐dependent vasodilatory pathway that is altered in preeclamptic vessels.…”
Section: Impaired Vasodilation In Pe Could Be Related To Decreased α2mentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note, however, that NO still plays a role in the vasodilation of the placental vasculature. Indeed, endothelium‐independent vasodilation, expressed as the vasodilatory response to the NO donor SNP, although reduced, was still present in preeclamptic placental vessels . This indicated that it might be the smooth muscle portion of the NO‐dependent vasodilatory pathway that is altered in preeclamptic vessels.…”
Section: Impaired Vasodilation In Pe Could Be Related To Decreased α2mentioning
confidence: 99%
“…NO is a principal vasodilator released by ECs and diffuses to the underlying VSMC layer triggering vasorelaxation . Because of its potency in mediating vasorelaxation, several studies aimed at understanding the role of NO in the isolated UA of PE animal models and in human placental vessels . However, these studies have revealed inconsistent results with controversy regarding the presence or absence of NO‐induced vasodilation in PE.…”
Section: Impaired Vasodilation In Pe Could Be Related To Decreased α2mentioning
confidence: 99%
See 3 more Smart Citations